The Mathematical Performance of At-Risk First Graders as a Function of Limited English Proficiency Status. (November 2019) - Martin, BrittanyLee N.; Fuchs, Lynn S.
The purpose of this study was to explore interactions between limited English proficiency (LEP) status, as a function of risk status (low math performance at the start of the school year), on computation and word-problem-solving performance. Among 260 first-grade students, classified as at-risk (AR) or not-at-risk (NAR) for math disability, we compared the performance of LEP students with native-English-speaking peers. A series of two-way ANOVAs were conducted on computation and word-problem-solving skills at two time points, fall and spring of first grade. On fall computation measures, there was no main effect for LEP status and no interaction between LEP and risk status. On spring computation, a main effect for LEP status had emerged, but again no interaction. By contrast, on fall word-problem solving, there was an interaction between LEP and risk status; however, this interaction was no longer significant by spring. Results suggest that language proficiency is an important factor in the development of computation and word-problem-solving skill. Implications for future research are discussed.